Different Patterns of Bacterial Species and Antibiotic Susceptibility in Diabetic Foot Syndrome with and without Coexistent Ischemia - Rafał Małecki; Kamil Klimas; Aleksandra Kujawa (Journal of Diabetes Research)
Aims. Infection in diabetic foot syndrome (DFS) represents serious medical problem, and the annual risk of DFS in diabetic patients is 2.5%. More than half of the patients with DFS have symptoms of extremity ischemia (peripheral arterial disease (PAD)). The aim of the present study was to analyze the frequency of particular bacterial strains in people with DFS, analyze the impact of arterial ischemia on the occurrence of a given pathogen, and evaluate the antibacterial treatment based on the results of bacterial culture. Methods. The analysis included 844 bacterial strains obtained from 291 patients with DFS hospitalized in the Department of Angiology in years 2016–2019. Results. The most common isolates were Staphylococcus aureus, Enterococcus faecalis, Enterobacter cloacae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Nearly 20% of the species were found to have at least one resistance mechanism. In patients with PAD, Gram-negative species were isolated more commonly than in people without PAD. The most useful drugs in DFS in hospitalized patients are penicillins with beta-lactamase inhibitors, 3rd- to 5th-generation cephalosporins (with many exceptions), carbapenems, aminoglycosides, and tigecycline. Conclusions. Bacterial strains isolated from ischemic DFS are more resistant to commonly used antibacterial agents, i.e., penicillins (including penicillins with beta-lactamase inhibitors), cephalosporins (except for the 4th and 5th generations), glycopeptides, and linezolid. When planning treatment of hospitalized patients with DFS, the presence of ischemia in DFS should always be taken into consideration. It determines the occurrence of particular bacterial species and the choice of antibacterial agent and may determine the rate of treatment success.